Mechanism-resolved operating windows for biochar production from lavender distillation residue - Soomro, Ahsanullah; Kocer, Anil Tevfik; Hassan, Mahdi; Balkanli, Didem (SPRINGER SINGAPORE PTE LTD, 2026)
Lavender distillation residue is an underutilized lignocellulosic carbon waste with strong potential for value-added conversion to biochar; however, pyrolysis operating windows are often selected using end-point product metrics alone, with limited mechanistic grounding and weak integration of energy and environmental burdens. Here, a 13-run N-2 pyrolysis design space (200-600 degrees C; 10-40 degrees C min-1; 0-30 min hold) was evaluated to develop a mechanism-resolved operating-window framework coupling thermal fingerprints, conversion-dependent kinetics, and decision-oriented screening. Thermogravimetric analysis revealed heating-rate-dependent DTG peak migration (Tmax approximate to 327 -> 364 degrees C for 5 -> 40 degrees C min-1). DTG overlap was quantified using constrained multi-peak deconvolution with information-criterion selection, showing beta-dependent statistical resolvability (two peaks at 5-10 degrees C min-1; three peaks at 20-40 degrees C min-1) consistent with overlap-limited separability rather than a literal reaction count. ICTAC-aligned isoconversional kinetics (KAS/FWO/Starink/Friedman) indicated regime evolution: apparent activation energies were comparatively stable through alpha = 0.1-0.6 but increased sharply at high conversion (alpha = 0.9), consistent with late-stage carbonization where derivative sensitivity increases. Across the matrix, final temperature exerted the dominant first-order control on the yield-carbonization trade-off. To translate mechanistic insight into actionable selection, electricity-normalized indicators and gate-to-gate EF3.0 midpoint burdens were integrated via entropy-weighted TOPSIS, identifying Run 5 as the best-compromise operating point (48.94% yield; 0.85 kWh kg-1 char; 2.05 kWh kg-1 fixed-C). Imposing an FC >= 60% constraint shifted the preferred option to Run 4 (61.67% fixed carbon; 8.16 kWh kg-1 fixed-C). Overall, the study provides a reproducible pathway from thermal fingerprinting to kinetic regime diagnosis and energy/LCA-informed operating-window selection, enabling defensible process design for lavender-residue biochar valorization.
Keywords: Lavender distillation residue; Pyrolysis; Thermogravimetric analysis (TGA/DTG); Isoconversional kinetics; Environmental footprint 3.0 (EF3.0) gate-to-gate life cycle assessment; EWM-TOPSIS (multi-criteria decision analysis); KINETIC-ANALYSIS; MASTER PLOTS; BIOMASS; WASTES; ENERGY; CHAR; Environmental Sciences & Ecology; Agriculture